Report from the Committee of Secrecy, appointed to take into consideration the treasonable papers presented to the House of Commons of Ireland, on the twenty-ninth of April last. Reported 10th May 1797, by the Right Hon. Mr. Secretary Pelham. To which is added, a charge to the grand jury of the county of Dublin, by Robert Day, Esq (Stockdale, 1797)
With: Report from the Committee of Secrecy of the House of Lords of Ireland.